Fire Behavior in Pelalawan Peatland, Riau Province - BAMBANG HERO SAHARJO (Society for Indonesian Biodiversity, 2006)
During dry season it is easily recognized that smoke will emerge at certain place both in Sumatra and Kalimantan that is in peatland. The worst situation occurred when fire burnt buried log in the logged over area where the fire fighter did not have any experience and knowledge on how to work with fire in peatland. Finally it had been found that one of the reasons why firefighter failed to fight fire in peatland is because they do not have any knowledge and experience on it. In order to know the fire behavior characteristics in different level of peat decomposition for fire management and sustainable management of the land for the community, research done in Pelalawan area, Riau Province, Indonesia, during dry season 2001. Three level of peat decomposition named Sapric, Hemic, and Fibric used. To conduct the research, two 400 m2 of plot each was established in every level of the peat decomposition. Burning done three weeks following slashing, cutting and drying at different time using circle method. During burning, flame length, rate of the spread of fire, flame temperature and following burning fuel left and the depth of peat destruction were measured. Results of research shown that in sapric site where sapric 2 has fuel load 9 ton ha-1 less than sapric 1, fire behavior was significantly different while peat destructed was deepest in sapric 2 with 31.87 cm. In hemic site where hemic 2 has fuel load 12.3 ton ha-1 more than hemic 1, fire behavior was significantly different and peat destructed deeper than hemic 1 that was 12.6 cm. In fibric site where fibric 1 has fuel load 3.5 ton ha-1 more than fibric 1, fire behavior was significantly different that has no burnt peat found. This results found that the different fuel characteristics (potency, moisture, bed depth, and type) at the same level of peat decomposition will have significantly different fire behavior as it happened also on the depth of peat destruction except fibric. The same condition occurred in the fire behavior at different level of peat decomposition. Key words: Fire, fuel, peat, sapric, hemic, fibric, Pelalawan.